Struktur Mikro Sintaksis Takarir Instagram Ridwan Kamil dan Ganjar Pranowo - Silvia Ratna Juwita; Dadang S. Anshori; Vismaia S. Damaianti; Yeti Mulyati; Oktian Fajar Nugroho; Nurul Febrianti; Imam Sutanto (Badan Pengembangan dan Pembinaan Bahasa, 2024)
Instagram is one of the social media of choice for 1.39 billion active users, including regional leaders who use this platform to convey information through captions in their content. The captions of Ridwan Kamil and Ganjar Pranowo, as regional heads with millions of followers, were chosen by researchers to be analyzed using a qualitative approach and critical discourse analysis (AWK) developed by Teun A. Van Dijk. Data taken from the Instagram captions of the two regional heads during the Cianjur earthquake disaster period at the end of November 2022 and the 2023 New Year's Eve floods that occurred in Semarang. The aim of this research is to identify the syntactic microstructure of regional leaders' Instagram caption discourse, which includes: (1) coherence, (2) sentence structure, and (3) use of pronouns. The results of the research show that there are similarities and differences in the estimates of the two regional leaders on each microstructural element. In Ridwan Kamil, elements of causal and positive coherence, active and passive sentence forms, as well as the use of the pronouns